Identification of Oxindoleacetic Acid Conjugates in Quinoa (Chenopodium quinoa Willd.) Seeds by High-Resolution UHPLC-MS/MS - Karonen, Maarit; Pihlava, Juha-Matti (MDPI AG, 2022)
Quinoa (Chenopodium quinoa Willd.) has a high nutritional value and it contains a high number and high amounts of specialized metabolites. These metabolites include, for example, phenolic acids, flavonoids, terpenoids and steroids. In addition, it is known to contain N-containing metabolites, such as betalains. Here, we report the presence and identification of 14 new oxindoleacetate conjugates in quinoa by high-resolution ultrahigh-performance liquid chromatography quadrupole-time-of-flight tandem mass spectrometry (UHPLC-QTOF-MS/MS) and ultrahigh-resolution UHPLC-QOrbitrap-MS/MS. The oxindoleacetate conjugates were extracted from dried and ground quinoa seeds using either methanol/water or acetone/water (4:1, v/v) and were further concentrated into aqueous phase and analyzed by UHPLC with reverse-phase chromatography using acetonitrile and 0.1% aqueous formic acid as eluents. High-resolution hybrid LC-MS/MS techniques, including full scan MS with in-source collision, induced dissociation, and data dependent-MS2(TopN) with stepped normalized collision energies using N2 as collision gas and data-independent acquisition (MSE) using ramped collision energies and argon as collision gas enabled their analysis directly from the crude quinoa seed extract. The oxindoleacetate conjugates were found to be present in both conventional and organic farmed seeds. According to our best knowledge, this is the first time hydroxy-oxindoles have been reported in quinoa.
Keywords: Chenopodium quinoa; indoleacetic acid; phenolic acids; phenolics; UHPLC-QOrbitrap; UHPLC-QTOF